The MYC transcription factors are involved in regulating the time-of-day variations in susceptibility to Botrytis cinerea in Arabidopsis thaliana - Joseph, Rageema (Department of Molecular and Cell Biology, 2022)
Plants are exposed to pathogens at specific, yet predictable times of the day-night cycle. The circadian clock, an endogenous timing mechanism, allows plants to anticipate recurring changes in pathogen abundance. A recent study showed that in Arabidopsis thaliana (hereafter: Arabidopsis), the circadian clock influences temporal differences in susceptibility to the necrotrophic pathogen, B. cinerea. Plants were less susceptible following inoculation at subjective dawn compared to subjective midnight. Based on the time required for B. cinerea spores to germinate and hyphae to penetrate host tissue and infect plants, infection takes place approximately 12 hours after inoculation. The jasmonic acid (JA) pathway regulates immune responses against B. cinerea. The paralogous basic helix-loop-helix transcription factors, MYC2, MYC3 and MYC4 are primary regulators of the JA pathway and have been implicated in immune responses against B. cinerea but it is not known whether any or all of these transcription factors are involved in regulating time-of-day variations in susceptibility. This study aimed to investigate whether MYC2, MYC3, and MYC4 are involved in the timeof-day differences in susceptibility to B. cinerea, and if they serve as molecular links to regulate interactions between the JA pathway and the circadian clock in Arabidopsis. In this work, the wild-type temporal variation in susceptibility was abolished in the myc234 triple mutant coupled with increased susceptibility following inoculation at both times of the day. The presence of MYC2, MYC3 or MYC4 alone was sufficient to maintain the wild-type time-of-day differences in susceptibility. Constitutive expression of MYC2, MYC3 or MYC4 abolished time-of-day differences in susceptibility but had different effects on overall susceptibility; constitutive expression of MYC2 and MYC4 decreased susceptibility while constitutive expression of MYC3 increased susceptibility to B. cinerea. Gene expression analyses performed on leaves revealed that the transcripts of MYC2 and MYC3 but not MYC4 are expressed rhythmically with peak transcript abundance timed to discrete times of the day under both light-dark and constant light conditions. Constitutive expression of circadian clock genes CCA1 and TOC1 abolished rhythmic MYC expression. The circadian clock modulates rhythmic leaf movement and rhythmic leaf movement was abolished in plants with constitutive MYC2 and MYC3 expression but not in plants with constitutive MYC4 expression and/or in the myc234 triple mutant. Altogether, the data suggest that the MYCs are involved in circadian-driven defence responses against B. cinerea. More specifically, MYC2, MYC3 and MYC4 function redundantly in regulating time-of-day differences in defence responses. In addition, the MYCs function as a point of convergence between the JA pathway and the circadian clock. MYC2 and MYC3 (but not MYC4) may be involved in reciprocal interactions between the JA pathway and the circadian clock.